Electrolysis Using Magnesium and Copper Electrodes: A Study of Voltage, Current, and Light Intensity - Amarullah; Achmad Afandi; Ulika Trijoga Putrawardana; Ulil Masruroh; Yoga Kriswahyudi; Muhammad Furqon (Politeknik Negeri Madura, 2025)
This research aims to develop a lighting system that utilizes seawater as an electrical energy source through the electrolysis process. Two metals, copper and magnesium, are used as electrodes that generate DC voltage when immersed in seawater. The output voltage from this process is relatively low, so a boost converter circuit is employed to increase the voltage level sufficiently to power a lamp. The converter circuit is designed using electronic components such as an inductor, diode, capacitor, and transistor to regulate and stabilize the output voltage. The experimental results show that the system can produce up to 5 watts of power and successfully illuminate a lamp with optimal brightness. This study demonstrates that combining seawater electrolysis with an electronic voltage-boosting circuit can serve as a simple and effective renewable energy alternative, particularly for coastal areas that are not yet connected to conventional electricity networks.